Turismo y re-creación étnica en la selva peruana - Plasencia Soto, Rommel (2007)
The observation of indigenous societies in the Amazonia give us a firm basis to make precisions about the anthropology of tourism, understood as a guided, organized and anchored glance at exotic representation and cultural consumption.